Students' Perceptions of Online Learning in the History Education Program - Dokolamo, Hamid; Hetharion, ‪Bety Diana; Rehena, Matheos (JENDELA PENGETAHUAN, 2022)
Perceptions of History Students on Online Learning in the History Education Study Program. This research aims to see how the perception of students of the history education study program toward online learning that takes place in the history education study program. This research is a descriptive qualitative approach that reveals in-depth the implementation of online learning. Data collection techniques were collected through interviews, observations, and documentation studies. The results of this study are in the implementation of learning, 95% of students have a favorable opinion, meaning that there are no obstacles to get. In contrast, in students' perceptions of learning, three points are measured: 1. The effectiveness of 90% of students have a positive perception where students feel the ability to play technology increases in learning online. Communication: 60% of students have a negative perception of students feeling that communication in online learning is not going well. While 66% of students positively perceive feedback, the reciprocal relationship between students and lecturers is going well. Constraints encountered by students in online learning are internet connection, high cost, lots of assignments, non-conducive learning environment, and less effective learning.